Environmental Impact of Ground Source Heat Pumps versus Air Source Heat Pumps in different climates - Aresti, Lazaros; Christodoulides, Paul (My University, 2024)
The Ground Source Heat Pump (GSHP) consists of Ground Heat Exchangers (networks of underground tubes with a circulating refrigerant fluid), coupled with a heat pump. Thus, GSHPs form one of the most popular forms of Shallow Geothermal Energy, used for heating and cooling of buildings. They generally exhibit higher efficiencies than conventional air-source heat pumps. Putting cost aside, the goal in the current paper is to present an analysis, through a Life Cycle Assessment, for the environmental impact of such systems through a comparison between seven European countries. The outcome points to the usefulness of adopting GSHP technologies in most climate zones on Europe.
Keywords: nearly Zero Energy Buildings; Life Cycle Analysis; Ground-source heat pumps